Parallelism in energy production through interior architecture sustainable development. (18th December 2017) - Osama, Mohamed; Helaly, Mohamed
Abstract: The advanced aspect of technology and the digital revolution is influencing not just the way we draft, additionally how to rethink, to create a new generative architecture. Such expressionistic, evolutionary, emergent structures would have been unfathomable without higher innovation, allowing an abundance of experimentation, any structure appears conceivable, the architectural dialect changed, and the way outline thinking has different measurements. Computer architecture employs the ability to model force and flow in order to parameterize the design properties. By understanding form and materials not as static or inanimate, but as engaged in complex behaviour, moreover the computer has turned into a generally acknowledged component both of architecture and the design process due to its extensive outcomes and impact on the structures. It introduces a wide range of methodologies and spectrum of approaches; As computer will drastically change how we design. This paper will discuss the roots of computer architecture. Also, to learn about the structures brought by the integration between computer and design and theorizing: the design process by investigating at the main lines of the development of computer architecture in architecture design. Abstract : This graphical abstract represents the generative design approach used in this research.